Case Report: A multidisciplinary, protocol-driven pathway from recurrent pregnancy loss to live birth in an anti-Ro/SSA-positive primary Sjögren’s syndrome pregnancy with literature review - Zhang, Jing; Chen, Jianhong; Li, Sheng-Guang; Liu, Xiangyuan (Frontiers in Immunology, 2026)
BackgroundMaternal anti-Ro/SSA (Sjögren's syndrome-related antigen A) [± anti–La/SSB (Sjögren's syndrome type B antigen)] antibodies can lead to neonatal lupus, which may present most severely as autoimmune congenital atrioventricular block (CAVB). Although CAVB is uncommon (~ 2% of anti-Ro/SSA-positive pregnancies), once a complete block develops, spontaneous reversal is rare, and many affected infants require permanent pacemaker implantation. Consequently, prevention and early detection are critical components of management, particularly in pregnancies following previous antibody-mediated losses.Case presentationA 34-year-old woman with primary Sjögren’s syndrome, high-titer anti-Ro/SSA and anti-La/SSB, and a history of five prior pregnancy losses—two early (biochemical, 7 weeks) and three midtrimester (16–21 weeks) complicated with severe fetal complete heart block (one demise, two terminations for hydrops)—presented for her sixth pregnancy. A multidisciplinary protocol was implemented, including hydroxychloroquine 400 mg/day, methylprednisolone (initially 6 mg/day, briefly increased to 32 mg/day at 14–16 weeks, then tapered to 8 mg/day), low-dose aspirin 50 mg/day, and fondaparinux 2.5 mg/day from ovulation throughout pregnancy, along with scheduled intravenous immunoglobulin (IVIG; 20 g at 4, 6 + 6, and 8 + 2 weeks; followed by 20 g/day × 3 at 14, 18, and 22weeks). From 14weeks, weekly fetal echocardiography with Doppler atrioventricular (AV)-interval monitoring (16–26weeks) remained normal. At 38 + 2weeks, a cesarean section delivered a female infant weighing 2,710 g and measuring 49 cm, with Apgar scores of 9/10. Neonatal telemetry/ECG showed sinus rhythm at 144 bpm without AV block. Echocardiography revealed a patent ductus arteriosus and a small atrial septal defect, with moderate pulmonary hypertension (SPAP 51 mmHg). Brain MRI and EEG were normal, and there were no cutaneous, hepatic, hematologic, or other features of neonatal lupus. Postpartum, the mother continued methylprednisolone 6 mg/day, hydroxychloroquine 400 mg daily, and enoxaparin 4,000 IU once daily for 4 weeks maintain disease suppression and thromboprophylaxis.ConclusionIn an anti-Ro/SSA-positive pregnancy at extreme risk, a prevention-first, protocol-driven approach—centered on hydroxychloroquine, judicious immunomodulation, and structured AV-interval surveillance—successfully averted CAVB and resulted in a pacemaker-free live birth. Minor cardiac lesions warrant ongoing follow-up; however, the absence of conduction disease underscores the clinical utility of this strategy in carefully selected, extreme-risk pregnancies.